Transient Osteoporosis During Pregnancy: The Perioperative Nurse’s Role - Labricciosa, Antoinette (Operating Room Nurses Association of Canada Journal, 1998)
Perioperative nurses are confronted with ever changing demands in their daily practice. Perhaps the greatest challenge, however, is in the care of patients with multi—faceted health problems. These patients require the coordination of many multi-disciplinary team members in attempting to achieve optimum health. This paper will describe the case study of a 28 year old, 26 week primip, who presented to a tertiary care centre with spontaneous bilateral hip fractures of unknown origin. It will further discuss the disease process known as Transient Osteoporosis during Pregnancy, the surgical approach, and finally, the role of the perioperative nurse in coordinating the patient’s perioperative care.